TRANSFORMATION OF CAFETERIA SERVICES THROUGH CASHLESS TRANSACTIONS AT IMBOS ISLAMIC BOARDING SCHOOL PRINGSEWU LAMPUNG - Huda, Ahmad Nur; Noviarita, Heni (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The development of digital technology has encouraged various sectors, including education, to adopt cashless transaction systems to improve financial efficiency and transparency. This research aims to analyze the transformation of canteen services through the implementation of a cashless transaction system at Pondok Pesantren IMBOS Pringsewu. The research method used is a qualitative approach with a case study design. Data were collected through observation, interviews, and analysis of related documents. The research results show that the implementation of a cashless transaction system based on digital student cards has a significant positive impact. Transaction efficiency increased with faster service times, shorter queues, and more accurate financial record-keeping. This system also allows students to be more independent in managing their finances. However, there are several challenges in its implementation, such as limited internet access, limited transaction devices at each tenant, and resistance from some students and canteen managers who are still accustomed to the cash system. To address these challenges, strengthening digital infrastructure, providing adequate transaction tools, and enhancing digital literacy for students and canteen managers are necessary. Overall, the implementation of cashless transactions at the IMBOS Pringsewu Islamic Boarding School canteen contributes positively to supporting service efficiency and financial transparency, and serves as a model for other boarding schools in adopting a financial digitalization system.